2018
DOI: 10.1016/j.gene.2018.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the abundance of bacterial genes related to dimethylsulfoniopropionate catabolism in seawater from Ofunato Bay revealed by metagenomic analysis

Abstract: Ofunato Bay is located in the northeastern Pacific Ocean area of Japan, and it has the highest biodiversity of marine organisms in the world, primarily due to tidal influences from the cold Oyashio and warm Kuroshio Currents. Our previous results from performing shotgun metagenomics indicated that Candidatus Pelagibacter ubique and Planktomarina temperata were the dominant bacteria (Reza et al., 2018a, 2018b). These bacteria are reportedly able to catabolize dimethylsulfoniopropionate (DMSP) produced from phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…We observed high abundance of Candidatus Pelagibacter in May compared to the September sample. Such changes in abundance may depend on different environmental factors, such as interactions with phytoplankton, availability of dissolved organic matter (DOM), grazing by eukaryotes, or predation by viruses [20,21]. Besides the SAR11 clade, we also found halophylic Alphaproteobacterium Maricaulis belonging to the Rhodobacteriales order, the bacteria described to be widely distributed in marine habitats and considered to be rapid surface colonizers in ocean waters [22].…”
Section: Microbial Diversitymentioning
confidence: 83%
“…We observed high abundance of Candidatus Pelagibacter in May compared to the September sample. Such changes in abundance may depend on different environmental factors, such as interactions with phytoplankton, availability of dissolved organic matter (DOM), grazing by eukaryotes, or predation by viruses [20,21]. Besides the SAR11 clade, we also found halophylic Alphaproteobacterium Maricaulis belonging to the Rhodobacteriales order, the bacteria described to be widely distributed in marine habitats and considered to be rapid surface colonizers in ocean waters [22].…”
Section: Microbial Diversitymentioning
confidence: 83%
“…Until now, no molecular studies had investigated DMSP production and cycling in estuarine environments. However, many studies have investigated DMSP catabolism via the analysis of microbial communities and their catabolic gene abundance, distribution and transcription in diverse marine samples (Howard et al ., 2008; Levine et al ., 2012; Kudo et al ., 2018; Liu et al ., 2018), including some focused on estuarine regions (Williams et al ., 2019; Han et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pelagibacter depends on reduced sulphur compounds such as dimethylsulfoniopropionate (DMSP), which originate from phytoplankton 63 , 64 . Kudo et al 31 reported that a high abundance of the DMSP catabolic gene dmdA in Ca . Pelagibacter ubique HTCC1062 in Ofunto Bay were correlated with spring phytoplankton blooms.…”
Section: Discussionmentioning
confidence: 99%